Economic performance of smallholder goat farmers under the Farmer FIRST Programme - R., Hari; Meena, Chetan; Singh, S. R. K.; Upadhyay, Devesh; Prajapati, Priyanka (Indian Farming, 2025)
Goat farming serves as an important livelihood source for small and marginal farmers in Madhya Pradesh, ensuring income generation and nutritional security. The present study evaluated the economic performance of smallholder goat farmers under the ICAR Farmer FIRST Programme (FFP) implemented in Jabalpur district. Data from 140 respondents comprising FFP beneficiaries, nonbeneficiaries within project villages, and farmers from non-FFP villages were analyzed for key economic indicators including fixed cost, variable cost, total cost, gross return, net return, gross income, and benefit–cost (B:C) ratio using one-way ANOVA and post-hoc tests. Results indicated no significant difference in fixed costs; however, FFP beneficiaries reported significantly lower variable costs and higher gross returns (`2842), net returns (`2268), and B:C ratio (4.14) than control groups. The study highlighted that FFP interventions improved profitability through efficient feeding, breeding, and health management. These findings validate participatory extension as a sustainable model for strengthening smallholder goat-based livelihoods.